ULMC-BSF: Underwater Laser Misalignment Channel Modeling Based on Beam Spread Function - Yang, Fan; Yi, Miaomiao; Yang, Xiao (IEEE internet of things journal, 2024)
Underwater wireless optical communication (UWOC) plays a crucial role in the Underwater Internet of Things (UIoT), offering exceptional bandwidth, extended communication ranges, and robust security capabilities through laser-based communication. However, it is imperative to account for the complex and dynamic underwater environment, particularly the impact of multiple scattering phenomena. To address this challenge, we introduce the underwater laser misalignment channel based on beam spread function (ULMC-BSF). This model comprehensively considers various factors such as absorption, multiple scattering, misalignment, and mixed exponential-generalized gamma (EGG) turbulence. To enhance modeling efficiency, we propose a semi-analytical exponential fitting approach. Compared to the traditional triple integration of the beam spread function (BSF) and Monte Carlo (MC) simulation methods, this approach significantly improves the computational efficiency of channel coefficients by approximately 4-5 orders of magnitude. Additionally, we apply the ULMC-BSF model to assess the outage probability and average bit error rate (ABER) of the asymmetrically clipped optical orthogonal frequency-division multiplexing (ACO-OFDM) system. Extensive MC simulations verify that the theoretical performance based on ULMC-BSF closely aligns with the MC results. Notably, in coastal oceans where an ABER level of 10−4 is achieved, the ULMC-BSF model exhibits superior modeling accuracy. Specifically, it predicts a lower transmit power by approximately 3 dBm compared to the traditional laser misalignment channel based on Beer-Lambert law (TLMC-BL). This advantage is crucial for accurately assessing UWOC signal quality and provides a more precise and reliable foundation for optimizing network topologies and routing strategies, enhancing network connectivity, and designing efficient security algorithms.